RFID in the Supply Chain: A Guide to Selection and Implementation - Myerson, Judith (CRC Press, 2009)
Giving organizations the ability to track, secure, and manage items from the time they are raw materials through the life-cycle of the product, radio frequency identification (RFID) makes internal processes more efficient and improves overall supply chain responsiveness. Helping you bring your organization into the future, RFID in the Supply Chain: A Guide to Selection and Implementation explains RFID technology, its applications in SCM, data storage and retrieval, business processes, operational and implementation problems, risks, security and privacy, facility layout, handling systems and methods, and transportation costs. In short, with its soup-to-nuts coverage, the book ensures that your RFID implementation is successful and that you get the most from your investment.